If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6x + -13) = 0 Reorder the terms: 2(-13 + 6x) = 0 (-13 * 2 + 6x * 2) = 0 (-26 + 12x) = 0 Solving -26 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 12x = 0 + 26 Combine like terms: -26 + 26 = 0 0 + 12x = 0 + 26 12x = 0 + 26 Combine like terms: 0 + 26 = 26 12x = 26 Divide each side by '12'. x = 2.166666667 Simplifying x = 2.166666667
| log(x+13)-log(2)=log(2x+3) | | 43-2[6+(3+2)]= | | 0.03x+0.15(70)=0.15(82) | | 2x+x+6=8 | | Sin(2x)cos(x)=sin(x)cos(2x) | | -4/5(-19/16) | | 12+3[5+(4-2)]= | | |-5|= | | 0.0003x^2+2x+300= | | |11|= | | |-3|= | | 2ly+4x-x^2=0 | | 0.30x+22.00=112.00 | | -384+n=12 | | 6a-11=8+2a | | (2x-5)=255 | | 4x-10+2x=5+6x-14 | | -182+14=n | | 318=2(9-3w)+2w | | 3/10x=1/5=-2 | | 1-(8/k^3)=0 | | n+(-6)=22 | | 444=2(8-4w)+2w | | 153+n=17 | | 2/7y-8=11 | | 15-(x+7)=7x-8 | | 7/8-9/-8/2 | | 90+n=18 | | (2x-5)squared=255 | | x^2+20-y^2-9x-4y+21-8x+6y-2=3-4y-5x-2y^2 | | y=lntan(π/4-x/2) | | 81x^20-16y^8=0 |